Dystrophic Scoliosis with Rib Head Dislocation into Spinal Canal in Neurofibromatosis-1 and its Surgical Management: A Case Report - Boruah, Tankeswar; Kumar, Akhilesh; Kumar, Ramesh (Indian Journal of Case Reports, 2019)
Neurofibromatosis-1(NF-1) is one of the most common single-gene disorders in humans. Patients with NF-1 may present with a wide variety of clinical manifestations. Spinal deformity is the most common musculoskeletal manifestation of NF-1. Rib head dislocation into the spinal canal is not a common entity but if left untreated can lead to serious neurological complications. The present report describes thoracolumbar dystrophic scoliosis with rib head dislocation into the spinal canal in a 28-year-old male who presented with complaint of spinal deformity with gait disturbance. Cobb angles measured 92 degrees of scoliosis (T9-L2), and 110 degrees of kyphosis and also highlights the importance of preoperative planning and radiological imaging for the successful surgical outcomes and our experience of single-stage posterior deformity correction with pedicle screw construct along with rib head excision.